RHD and RHCE genes polymorphism: literature review - L. L. Golovkina; R. S. Kalandarov (Онкогематология, 2020)
The article provides a literature review about RHD and RHCE polymorphisms which encode different RhD and RhC antigen variants. The data about genes RHD and RHCE polymorphisms, RhD weak types, RhD partial types and RhC variants in Russians is presented for the first time. The molecular and serological characteristics of rare RhD and RhC antigens are summarized. The role of serological and molecular methods in Rhesus system antigens identifying is shown.